THE EFFECT OF PERCEPTION OF ORGANIZATIONAL SUPPORT AND JOB SATISFACTION ON EMPLOYEE ENGAGEMENT AT W HOSPITAL - Wise Rahmawan (Bajang Institute, 2024)
This study was conducted to determine how much influence the perception of organizational support and employee job satisfaction have. This study aims to analyze the simultaneous influence of perception of organizational support and job satisfaction on employees, analyze the partial influence of perception of organizational support on employee engagement, and analyze the partial influence of job satisfaction on employee engagement. To achieve the research objectives, questionnaires were distributed to obtain data for each variable to 58 employees. The influence of independent variables separately and together is determined by the regression equation shown from the variable score, after the data for each variable passes the validity, reliability, and normality tests. Regression equation and coefficient of determination (R2). The result of the coefficient of determination or (R2) is 0.629 which shows that 62.9% of employee engagement is influenced by perception of organizational support and job satisfaction. While 37.1% is influenced by other causes not examined in this study. the perception variable t count is 4.063 with sig. 0.000 <0.05, then the perception of organizational support has a significant effect on employee engagement. While for the satisfaction variable t count is 1.112 with sig. 0.271>0.05 then job satisfaction does not significantly affect employee engagement. So it can be concluded that the perception of organizational support significantly affects employee engagement and job satisfaction does not significantly affect employee engagement.